An Individualized, Perception-Based Protocol to Investigate Human Physiological Responses to Cooling - Coolbaugh, Crystal L.; Bush, Emily C.; Galenti, Elizabeth S.; Welch, E. Brian; Towse, Theodore F. (Frontiers in Physiology, 2018)
Cold exposure, a known stimulant of the thermogenic effects of brown adipose tissue (BAT), is the most widely tested method to study BAT physiology in adult humans. Recently, individualized cooling has been recommended to standardize the physiological cold stress applied across participants, but critical experimental details remain unclear. The purpose of this work was to develop a detailed methodology for an individualized, perception-based protocol to investigate human physiological responses to cooling. Participants were wrapped in two water-circulating blankets and fitted with skin temperature probes to estimate BAT activity and peripheral vasoconstriction. We created a thermoesthesia graphical user interface (tGUI) to continuously record the subject’s perception of cooling and shivering status during the cooling protocol. The protocol began with a 15 min thermoneutral phase followed by a series of 10 min cooling phases and concluded when sustained shivering (> 1 min duration) occurred. Researchers used perception of cooling feedback (tGUI ratings) to manually adjust and personalize the water temperature at each cooling phase. Blanket water temperatures were recorded continuously during the protocol. Twelve volunteers (ages: 26.2 ± 1.4 years; 25 % female) completed a feasibility study to evaluate the proposed protocol. Water temperature, perception of cooling, and shivering varied considerably across participants in response to cooling. Mean clavicle skin temperature, a surrogate measure of BAT activity, decreased (-0.99 °C, 95% CI: -1.7 to -0.25 °C, P = 0.16) after the cooling protocol, but an increase in supraclavicular skin temperature was observed in 4 participants. A strong positive correlation was also found between thermoesthesia and peripheral vasoconstriction (ρ = 0.84, P < 0.001). The proposed individualized, perception-based protocol therefore has potential to investigate the physiological responses to cold stress applied across populations with varying age, sex, body composition, and cold sensitivity characteristics.